Weak intramolecular C-H⋯H-B and C-H⋯Cl interactions in C-aminoboryl-o-carboranes - Nie, Yong; Miao, Jinling; Pritzkow, Hans; Wadepohl, Hubert; Siebert, Walter (Journal of organometallic chemistry, 2013)
Reactions of dilithio-o-carborane Li2C2B10H10 (generated in situ from o-carborane 1 and butyllithium) with aminodichloroboranes R2NBCl2 (R = Et, iPr) led to the corresponding mono- and/or bis-C-aminoboryl-o-carboranes. The molecular compositions of the new o-carborane derivatives follow from NMR and MS data as well as from X-ray diffraction analyses. The structures of the new carborane compounds feature combined weak intramolecular C-H⋯H-B hydrogen-hydrogen and C-H⋯Cl hydrogen-chlorine bonding in the solid state.
Gesehen am 22.11.2021